SISTEM KONTROL PADA ROBOT PEMINDAH BARANG TIPE CARTESIAN CORDINAT MENGGUNAKAN ARDUINO UNO R3 - Darmawan, Dwiki; Sutisna, Setya Permana; Sutoyo, Edi (AME (Aplikasi Mekanika dan Energi): Jurnal Ilmiah Teknik Mesin, 2018)
Robots are an option to help human jobs address issues of precision, security and flexibility. The robot arm becomes one of the robot types that can help human work. The robot arm controller research is to control the stepper motor's motion according to the command. Desai this cartesian coordinate robot is 2 axis that is X and Y axis. Control of this robot arm using Visual Basic 6.0 programming for controlled robot from PC to arduino Uno R3. Motor driver used is IC A4988, stepper motor movement got input from PC with software visual basic 6.0. to move the stepper motor. Data sent from PC to Arduino Uno R3 is a command from Visial Basic 6.0 with serial communication. The microcomputer reads the serial data input and sends a step value data to the stepper motor driver to move the robot arm. The end result of the robot arm controller research that has been achieved is the robot arm can be controlled with the command to enter the distance that will be run by stepper motor as the method of pemograman which is controlled through serial communication with Visual Basic 6.0. The test results show an average error 22.26531 for the left and 52.61111 for the right direction on X axis while for Y axis -5,36957 for the downward direction and 0.117647 for the upper direction